Pathologic Study of Soft Tissue Sarcoma Registered in Al-Najaf Governorate for Ten Years (2011-2020) - Ameen , Tuka Adil Mohammed; Al-Janabi , Prof. Dr. Asaad A. (Academic Journal of Clinicians, 2024)
Background: Pathogenesis of most of malignant Soft tissue neoplasms (STNs) STNs is still unknown. Recognition of trend and causes of STNs represents a significant issue among oncologists and pathologist. Availability of a modern, more logical histo-genetic classification and standard nomenclature now offers a better clinico-pathologic correlation. Objective: To identify the prevalence of malignant soft tissue tumors in the last ten years in Najaf according to the type, location of tumor, age and sex of the patients. Methods: This was a cross-sectional study carried out at Kufa Training center of the Iraqi Council for medical specialization included almost all cases of malignant soft tissue tumors in Najaf for the period 2011 – 2020. Results: A total of 313 cases were reported, of them 174 (55.6%) males and 139 (44.4%) were females . The more frequent malignancy in both genders was Liposarcoma , followed by Rhabdomyosarcoma , Leiomyosarcoma, Fibrosarcoma, MFH and Synovial sarcoma, with an overall prevalence rate of 24.9% , 16.3%, 15.3%, 10.9%, 9.0% and 7.0%, respectively. while the least frequent type was ASPS.The highest prevalence rate 12.8% was found in 2017 and the lowest prevalence rate 7.4% in 2012. Majority of cases in all types were of grade 1 which contributes for 59.1% The higher recurrence rate reported in Dermatofibrosarcoma protuberans cases. Lower limbs were the most common site for the whole malignancies (25.6%) with the shoulder being least common site (4.2%) . Conclusion: Malignant soft tissue tumors registered in Najaf governorate are still rare tumors with Liposaercoma being the most common type and Males are more frequently affected. Lower extremities are the most affected site